Competencias argumentativas de los estudiantes de derecho en el marco de las pruebas Saber-Pro. (2015)
In the context of university training of lawyers, argumentative skills are vital for the outstanding performance of these professionals in their work environment; so the State sphere has tended to design, collecting the Saber-Pro test model, generic and specific evaluation components that support the appropriation of reading and writing and literacy skills in law students who face the State exam. In this research paper it is intended to inform the academic community about the indicators of performance on Saber-Pro tests, reflected by the students attached to the Law Program at Institución Universitaria de Envigado, seen from the analysis of argumentative skills.